2022
DOI: 10.1186/s40798-021-00364-0
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment, Management and Prevention of Calf Muscle Strain Injuries: A Qualitative Study of the Practices and Perspectives of 20 Expert Sports Clinicians

Abstract: Background Despite calf muscle strain injuries (CMSI) being problematic in many sports, there is a dearth of research to guide clinicians dealing with these injuries. The aim of this study was to evaluate the current practices and perspectives of a select group of international experts regarding the assessment, management and prevention of CMSI using in-depth semi-structured interviews. Results Twenty expert clinicians working in elite sport and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The use of large animal models in sheep to study skeletal muscle injury has been previously described, such as VML [ 28 ] and biceps femoris [ 29 ] injury models. However, their use for the study of calf injuries, which are highly prevalent among athletes and contribute negatively to their performance [ 35 , 36 ], has been overlooked. In our sheep muscle injury model, surgical incisions and opening tissue layers are not necessary to induce muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…The use of large animal models in sheep to study skeletal muscle injury has been previously described, such as VML [ 28 ] and biceps femoris [ 29 ] injury models. However, their use for the study of calf injuries, which are highly prevalent among athletes and contribute negatively to their performance [ 35 , 36 ], has been overlooked. In our sheep muscle injury model, surgical incisions and opening tissue layers are not necessary to induce muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent research has highlighted the association between low Plantar flexor strength and Achilles tendinopathy patients [3,[5][6][7][8][9][10][11], whilst other studies have shown the importance of Plantar flexor function to patient-reported outcomes post Achilles tendon rupture [12][13][14]. The existing literature reports an association between these injuries and reduced Plantar flexor power, with some prospective studies reporting the existence of deficits pre-injury [3], supporting the notion that Plantar flexor weakness may increase the risk of certain lower limb disorders [3,15,16].…”
Section: Introductionmentioning
confidence: 96%
“…Specific instructions and cues have been a key consideration in contemporary research and clinical settings to help standardise practice [11]. Performance and technique cues during the SLHR test may alter the number of repetitions to failure performed and potentially provide a more robust indication of an individual's capacity when screening athletes [12,13]. Although the longheld clinical hypothesis that cueing is warranted is yet to be substantiated in Australian football players [12].…”
Section: Introductionmentioning
confidence: 99%
“…Performance and technique cues during the SLHR test may alter the number of repetitions to failure performed and potentially provide a more robust indication of an individual's capacity when screening athletes [12,13]. Although the longheld clinical hypothesis that cueing is warranted is yet to be substantiated in Australian football players [12]. Whether cueing the SLHR test in this population significantly impacts test outcomes and the practical interpretation of theresults between conditions is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation